Use of virtual reality medical hypnosis for anxiolytic purposes during frozen embryo transfer: A prospective pilot study - Octavia Pingault; Annaëlle Testud; Elsa Labrune; Bruno Salle; Mehdi Benchaib; Éloïse Fraison (PLoS ONE, 2026)
Objective To assess the feasibility of using a virtual reality medical hypnosis (VRH) device for anxiolytic purposes during frozen embryo transfer (FET) and to observe its effect on subsequent pregnancy rate. Design This is a prospective, single-center study conducted in a French public reproductive medicine ward between December 2023 and 1 May 2024. Subjects Women aged 18–45 years who undergoing IVF at the center. The present study included 50 women who had a scheduled FET. Interventions Study participants were using the VRH device during the FET. Main outcomes measures Feasibility was defined as optimal and incident-free device use. Anxiety levels were measured pre- and post-procedure using the State-Trait Anxiety Inventory (STAI-Y1). Women and caregiver satisfaction were assessed using Likert scales, while acceptability of the procedure was assessed by recording adverse events. HCG test was conducted afterward and compared with a concurrent non-exposed cohort from the same unit and inclusion period using causal inference to analyze pregnancy rates. Results 50 women were included from the active patient file undergoing FET at the center. The feasibility of using the VRH device was assessed at 96%, with 100% acceptability of the procedure. Women satisfaction was 98%, and caregiver satisfaction reached 100%, with a favorable device’s use opinion in routine practice. A significant reduction in anxiety was observed, with a mean anxiety score of 28.8/80 after the procedure compared to 39.3/80 before (p < 0.001). Regarding pregnancy outcomes, 25 women had a positive HCG test after the procedure, including 20 with HCG > 100 IU/L, resulting in a pregnancy rate of 40%. Although a positive trend was observed in the comparison with the concurrent non-exposed cohort, the difference was not statistically significant (OR 1.18, 95% CI 0.65–2.14; p = 0.583). Conclusion The use of a VRH device during FET is feasible and safe, suggesting a promising anxiolytic effect and a useful non-medical tool for optimizing care pathways in assisted reproduction. Further larger and controlled studies are warranted to confirm these encouraging findings and to more thoroughly assess the impact on pregnancy outcomes.